2009
DOI: 10.1152/japplphysiol.91314.2008
|View full text |Cite
|
Sign up to set email alerts
|

The GABAA agonist muscimol attenuates induced airway constriction in guinea pigs in vivo

Abstract: Gleason NR, Gallos G, Zhang Y, Emala CW. The GABAA agonist muscimol attenuates induced airway constriction in guinea pigs in vivo. J Appl Physiol 106: 1257-1263, 2009. First published February 12, 2009 doi:10.1152/japplphysiol.91314.2008.-GABAA channels are ubiquitously expressed on neuronal cells and act via an inward chloride current to hyperpolarize the cell membrane of mature neurons. Expression and function of GABAA channels on airway smooth muscle cells has been demonstrated in vitro. Airway smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…Although we and others have characterized GABA effects on smooth muscle relaxation as well as GABA receptor expression in human airway (4,7,15,23), we are the first to investigate the source of GABA in the airway as illustrated in the present study. Three possible sources of GABA include airway epithelium, airway smooth muscle itself, and airway nerves.…”
Section: Discussionmentioning
confidence: 94%
“…Although we and others have characterized GABA effects on smooth muscle relaxation as well as GABA receptor expression in human airway (4,7,15,23), we are the first to investigate the source of GABA in the airway as illustrated in the present study. Three possible sources of GABA include airway epithelium, airway smooth muscle itself, and airway nerves.…”
Section: Discussionmentioning
confidence: 94%
“…GABA uptake can be decreased with cell membrane depolarization, similar to GAT in the CNS (25). These findings are of particular interest in the ASM, because depolarizing stimuli favor contraction of ASM, and we have previously shown that activation of GABA A channels can contribute to hyperpolarization and the subsequent relaxation of ASM (11,14,19). We further demonstrate that GATs in cultured human airway epithelial cells release 3 H-GABA under ionically favorable conditions, and that this release is significantly increased by cell membrane depolarization.…”
mentioning
confidence: 76%
“…The emerging evidence of a role for both GABA A channels and GABA B receptors in ASM (8,10,14,19) and epithelium (7,9) led us to question the mechanism(s) by which synthesized GABA could be released from airway cells, and whether cells other than epithelial cells (i.e., smooth muscle) could be a source of GABA in the airway. Specifically, we questioned whether ASM also expresses GAD, and whether airway epithelium and smooth muscle cells functionally express the vesicular GAT (VGAT) or any of the four known GATs.…”
Section: Clinical Relevancementioning
confidence: 99%
“…However, it has been a longstanding belief that any GABAergic contribution to airway tone was largely mediated by neurally mediated mechanisms (2,17,26). Our laboratory has demonstrated that airway smooth muscle GABA A receptor activation can both potentiate ␤-adrenoceptor agonist-mediated airway smooth muscle relaxation (in vitro) (7) as well as attenuate cholinergic-mediated airway resistance (in vivo) (8).…”
mentioning
confidence: 99%